Clinical and Radiographic Outcomes of C1 Laminectomy Without Fusion in Patients With Cervical Myelopathy That Is Associated With a Retro-odontoid Pseudotumor. Issue 10 (December 2016) - Takemoto, Mitsuru; Neo, Masashi; Fujibayashi, Shunsuke; Sakamoto, Takeshi; Ota, Masato; Otsuki, Bungo; Kaneko, Hiroki; Umebayashi, Takeshi
Abstract : Purpose: A retro-odontoid pseudotumor that is not associated with rheumatoid arthritis or hemodialysis is clinically rare. The majority of surgeons select transoral resection as the surgical treatment, often followed by posterior fusion or posterior decompression and fusion. In contrast, some authors have reported success with simple decompression without posterior stabilization in cases where atlanto-axial instability (AAI) is either absent or minor. In this study, we have evaluated the clinical and radiographic outcomes of C1 laminectomy without fusion as the surgical treatment for patients with cervical myelopathy that is associated with a retro-odontoid pseudotumor. Methods: A retrospective chart review was conducted on 10 patients who underwent C1 laminectomy without fusion for cervical myelopathy associated with a retro-odontoid pseudotumor. Results: The average follow-up time was 29 months. All cases were graded as Ranawat grade 3a or 3b. After surgery, myelopathy improved in all of the patients. In 2 patients, the atlas-dens interval increased in the flexed position; however, this did not result in any clinical problems. The size of the retro-odontoid mass (measured on magnetic resonance images at least 12 mo after surgery) decreased in 4 of the 10 cases. Conclusions: AAI progression and mass enlargement were our primary concerns for this surgical option; however, C1 laminectomy did not cause severe AAI progression, no patients showed serious mass enlargement, and all patients demonstrated neurological improvement. This surgical strategy is beneficial especially for elderly patients given the risks of other surgical options that use an anterior transoral approach or posterior fusion.